Fill in the blank sum_(m=2)^oo(m=5)(m+3)a_m x^(m+1)=sum_(m=blank)(blank) x^m

Mbalisikerc 2022-07-22 Answered
fill in the blank m = 2 ( m + 5 ) ( m + 3 ) a m x m + 1 = m = blank blank  x m
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

yatangije62
Answered 2022-07-23 Author has 16 answers
m = 2 ( m + 5 ) ( m + 3 ) a m x m + 1
here m + 1 = k m = k 1
So when m=2 k=3
k = 3 ( k 1 + 5 ) ( k 1 + 3 ) a k 1 x k
= k = 3 ( k + 4 ) ( k + 2 ) a k 1 x k
if we replace k by m, we get
= k = 3 ( m + 4 ) ( m + 2 ) a m 1 x m
so m=3
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions